205k views
5 votes
Simplify the expression below

6x3 + 5x2 + 3 – 4 (33 – 3x² + 2)
use^ in your answer to indicate a number raised.
Example: x^2 means x2
о 2x3 + 17x2 - 1
0
2x3 + 1722 - 5
7x3 + 1782 +5
O 7x3 + 17x2 - 7

User Engma
by
5.4k points

2 Answers

4 votes
  • Answer:

2x³ + 17x² - 5

  • Explanation:

Hi there !

6x³ + 5x² + 3 – 4 (x³ – 3x² + 2) =

= 6x³ + 5x² + 3 - 4x³ + 12x² - 8

= 6x³ - 4x³ + 5x² + 12x² + 3 - 8

= 2x³ + 17x² - 5

Good luck !

User Sang Nguyen
by
5.6k points
5 votes

Answer:

  • 2x^3 + 17x^2 - 5

Explanation:

Simplify:

  • 6x^3 + 5x^2 + 3 - 4 (x^3 - 3x^2 + 2) =
  • 6x^3 + 5x^2 + 3 - 4x^3 + 12x^2 - 8 =
  • (6x^3 - 4x^3) + (5x^2 + 12x^2) + (3 - 8) =
  • 2x^3 + 17x^2 - 5

Option B or second option is correct

Note. there is typo both in the question and the answer options

User Velu S Gautam
by
5.5k points